Criminal Responsibility for Domestic Violence Offenders in the Context of Suspected Adultery by the Wife - Adhyatma Noer; Hambali Thalib; Zainuddin Zainuddin (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the criminal responsibility of perpetrators of domestic violence in the context of alleged adultery by the wife, with a focus on how such allegations influence the proof of the element of fault in criminal law. The research employs an empirical legal approach aimed at understanding how legal norms operate in practice, particularly in handling domestic violence cases at the Makassar Metropolitan Police (Polrestabes Makassar). The findings indicate that allegations of adultery often function as a triggering factor for acts of violence due to emotional, social, and psychological dynamics within the household. However, from a criminal law perspective, such allegations do not possess juridical power to justify or eliminate criminal responsibility. The study reveals that the element of fault, particularly intent (mens rea), remains the central determinant in establishing criminal liability. The perpetrator’s conscious decision to commit acts of violence, despite being driven by emotional motives, fulfills the requirements of intentional wrongdoing. Furthermore, the legal system consistently rejects justifications based on emotional reactions, cultural values, or misinterpretations of religious teachings. The study also highlights challenges in the evidentiary process, particularly in proving psychological violence, and emphasizes the importance of expert testimony and documentary evidence such as visum et repertum. The research concludes that domestic violence cannot be justified under any circumstances, and legal enforcement must prioritize victim protection while maintaining the principles of justice, legal certainty, and expediency. Strengthening preventive measures, public awareness, and evidentiary regulations is essential to ensure more effective protection for victims